2021
DOI: 10.1111/tpj.15240
|View full text |Cite
|
Sign up to set email alerts
|

Phloem exudate metabolic content reflects the response to water‐deficit stress in pea plants (Pisum sativum L.)

Abstract: Summary Drought stress impacts the quality and yield of Pisum sativum. Here, we show how short periods of limited water availability during the vegetative stage of pea alters phloem sap content and how these changes are connected to strategies used by plants to cope with water deficit. We have investigated the metabolic content of phloem sap exudates and explored how this reflects P. sativum physiological and developmental responses to drought. Our data show that drought is accompanied by phloem‐mediated redir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The accumulation of homoserine, but not asparagine, in pea leaves under drought has been shown previously [39,51]. It is possible that the drought-induced changes in homoserine, asparagine, and glutamine content were due to a disruption of phloem transport [52,70].…”
Section: Amino Acidsmentioning
confidence: 68%
“…The accumulation of homoserine, but not asparagine, in pea leaves under drought has been shown previously [39,51]. It is possible that the drought-induced changes in homoserine, asparagine, and glutamine content were due to a disruption of phloem transport [52,70].…”
Section: Amino Acidsmentioning
confidence: 68%
“…This phenomenon can be partially explained by a decrease in the photosynthetic rate (reduction in CO 2 consumption) and an increase in the metabolic CO 2 production during stress. Our observations suggested that plants reduced water loss by limiting transpiration and attempted to cope with reduced energy production (the decrease in photosynthetic intensity) by increasing their catabolic processes and redistributing carbon [ 37 ]. Osmotic adjustment is an important mechanism of drought tolerance that helps retain water in plant tissues despite a low water potential [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can also play the role of reserves [ 121 ] and contribute to stress resistance [ 122 ]. A significant number of these were found in phloem exudates [ 114 , 115 , 116 , 123 , 124 ]. However, cell lines of only a few species are capable of utilizing sugar alcohols for growth supply.…”
Section: Organic Substratesmentioning
confidence: 99%